Building Organizational Pride through Corporate Social Responsibility - Yulianti, Praptini; Muzakki (International Journal of Psychosocial Rehabilitation, 2020)
CSR refers to organizational actions and policies to achieve financial, social environmental sustainable development. Sustainability in an organization can be achieved if an organization is not only focused on the macro level that organization profitability achievement, but also must have moral responsibility on government, society, and employees. This study objective is to examine on the micro level, in this case, is employee extra role behavior. Corporate Social Responsibility (CSR) in organizations can influence employee extra-role behavior or Organizational Citizenship Behavior (OCB) with mediating an employee pride in organizations or Organizational Identification (OID). This study is a quantitative study with spreading questionnaire among 140 manufacturing employees in Surabaya, Indonesia. The result of this study is that CSR has significance influenced to OID and OID has significance influenced OCB. This study implications is CSR indicates organizational care to government, society and surely, they will also care to the employee. CSR can influence attitude and behavior of employee. Employee will be pride as a part of organizations and have extra role behavior to organizational performance.